Digitalization Of Microfinance Institutions As A Solution For Community Economic Empowerment: Case Study Of BMD Syariah - Muhammad Ramaditya; Dewi Lusiana; Donny Oktavian Syah; Ardianto Muditomo; Dhanis Herlambang; Annisa Parastry (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This research is aim to provides a solution in the form of a mobile point-of-sale (MPOS) machine that can be integrated with the BMD Syariah Madiun Methodology/approach: This paper employs a design thingking process by having Focus froup discussion with all the management in BMD Syariah Madiun. Findings: The design and development of information technology solutions for innovation constraints considering the targeted value proposition, which is fast-cheap-easy. Fast, which means the speed in implementing solutions. Practical implications: One important step that BMD Syariah has taken is to develop an integrated business ecosystem, where every part of the organization is interconnected and supports each other. In this context, BMD Syariah strives to create an efficient and user-friendly payment system, where members can conduct transactions easily and quickly. Originality/value: Value proposition is a promise made by an BMD Syariah to customers regarding the benefits they will receive from the products or services offered with strong digitalization platform to its customer